BMI heritability and its relationship with puberty in 6 - 18-year-old twins - Tingting GUO; Yunjie BAI; Aiping FAN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo analyze the heritability of body mass index (BMI) and the impact of puberty on the heritability among twins aged 6 - 18 years in Shandong province. MethodsData on 453 pairs of child and adolescent twins of the same sex were collected from three counties/districts of Shandong province in November 2021. Univariate structural equation modeling was used to estimate the heritability of BMI. ResultsAfter adjusting for gender and age, the heritability of BMI in the twins was 0.88 (95% confidence interval [95%CI]: 0.80 - 0.88); the heritability of prepubertal BMI was 0.81 (95%CI: 0.74 - 0.86); and the heritability of BMI in late puberty was 0.88 (95%CI: 0.81 - 0.93). The heritability of BMI in prepubertal boys and girls was 0.77 (95%CI: 0.67 - 0.85) and 0.85 (95%CI: 0.77 - 0.91), and 0.92 (95%CI: 0.82 - 0.97) and 0.86 (95%CI: 0.76 - 0.92) in late puberty, respectively. ConclusionGenetic factors appear to play an important role in explaining the variation of BMI from prepuberty to late puberty, particularly in boys.